Flavour reformulation and flavour stability - Yang, Ni (2012)
ABSTRACT This project addressed two areas in the flavour industry – flavour reformulation required as a consequence of ingredient changes and flavour stability in solid food products. The aim of the flavour reformulation study was to evaluate both instrumental and modelling approaches to reformulate commercial flavourings for food products of different fat contents. A strawberry flavouring was chosen, which delivered an acceptable flavour in pectin jelly (0% fat) but did not perform so well in chewy candy (8% fat). Aroma release profiles in people eating these two sweets were measured by APCI-MS, the relative release differences for each flavour compound was determined and then used to reformulate the strawberry flavouring so its release in both sweets was similar. The sensory performance of candies confirmed a significant difference between the reformulated and original flavour (p < 0.05). The modelling approach was based on compound hydrophobicity (Log P) and the fat content of the food. This was used to estimate relative differences in flavour delivery for products with two varying fat contents. Flavourings were reformulated for yoghurt with reduce fat level, and the measured results showed good correlation with model’s prediction (r = 0.95). The aim of the flavour stability study was to explore the impact of product storage and flavour solvent in biscuits with vanilla flavouring. After eight weeks storage at 45 °C, up to 20% vanillin loss was measured, but sensory results suggested no difference in vanilla flavour perception. Texture analysis indicated that biscuits using triacetin (TA) as flavour solvent were more brittle than biscuits made with propylene glycol (PG). This was explained by X-ray CT analysis results which showed TA biscuits had larger pores than PG biscuits. Additionally, TA solvent provided higher vanillin stability during storage, so it should be a better choice than PG solvent used in flavourings for biscuits. IMPACT STATEMENT This research proved that it is feasible to apply laboratory-derived knowledge and adapt scientific techniques in a commercial context. It also demonstrated how the research findings can be transferred into the commercial field through two studies. The first study successfully illustrated two novel approaches to reformulate flavourings between food products of differing fat contents. Comparing with traditional trial and error process, this study demonstrated that instrumental and modelling approaches can be more effective ways for flavour reformulation in the flavour and food industry. The cost of flavour reformulation including the reformulation time and the cost in-use can therefore be reduced considerably. The results of this study have been presented to company’s major clients worldwide, and this has been applied commercially in a range of products including the successful reformulation of a £50 M (2010, brand value) soft drink into new formats (2011). The second study increased the understanding of the flavour stability within the stored food products. This ensured the flavour company to deliver high quality materials not only to their clients before food manufacturing, but also maintained its quality in the food products during storage for their end users. Comparing two flavour solvents – propylene glycol and triacetin, the results of this study suggested that triacetin is a better solvent as it offered better flavour stability in the stored biscuits. The findings can also be applied to reduce the cost in-use for vanilla flavouring in biscuit, which is especially beneficial for food and flavour company when high cost natural vanilla flavourings are required.